2019
DOI: 10.1038/s41598-019-46275-9
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected genetic diversity pattern and a complex demographic history of a rare medicinal herb, Chinese asparagus (Asparagus cochinchinensis) in Korea

Abstract: Range-wide population studies of wide spread species are often associated with complex diversity patterns resulting from genetically divergent evolutionary significant units (ESUs). The compound evolutionary history creating such a pattern of diversity can be inferred through molecular analyses. Asparagus cochinchinensis , a medicinally important perennial herb, is in decline due to overharvesting in Korea. Eight A . cochinchinensis populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…Fst values of different populations showed significant structuring of studied germplasm. Structure analysis showed two genetic stocks for the analyzed germplasm and in agreement to the results reported by Lee et al [ 36 ] in A. cochinchinensis . The two genetic stocks and very less admixture revealed by structure analysis strongly supported the species level demarcation of accessions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Fst values of different populations showed significant structuring of studied germplasm. Structure analysis showed two genetic stocks for the analyzed germplasm and in agreement to the results reported by Lee et al [ 36 ] in A. cochinchinensis . The two genetic stocks and very less admixture revealed by structure analysis strongly supported the species level demarcation of accessions.…”
Section: Discussionsupporting
confidence: 90%
“…A large number of this type of studies based on different DNA markers has been reported previously in various crops [ 27 , 38 , 39 ]. Dendrogram of A. adscendens and A. racemosus showed two major groups and agreed the results of Altintas et al, Castro et al, and Vijay et al [ 36 , 40 , 41 ] who also obtained two clades with different Asparagus species. Further examination of these groups revealed that group I was showing subgrouping in two subgroups while no such subgroups were observed in group II.…”
Section: Discussionsupporting
confidence: 90%
“…The higher the heterozygosity rate, the more similar the base sequence between two DNAs, and the closer the relationship between them [ 55 ]. The heterozygous rate of MO (average heterozygous rate = 32.26%) is significantly higher than other species, such as rice [ 56 ], soybeans [ 57 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, wind and animals have long been considered as the primary agents of inter-population gene exchange between geographically isolated populations, which can transport pollen and seeds to other MO plantations over the landscape, and can reduce the impact of genetic drift and founder events [60]. Since the gene flow that wind mediated appears to be effective just at distances of less than 1 km, anemochorous dispersal may only affect allele frequencies among closer populations, while birds can transport pollen and seeds over 12 km, and long-distance migration promotes gene flow between local populations, making the populations genetically homogeneous [55,61]. These are consistent with the results of field investigation: the plant morphological characteristics of Hainan population have significant variation, followed by Guangxi, while the plants of Guangdong and Fujian were similar.…”
Section: Discussionmentioning
confidence: 99%
“…belongs to the genus Asparagus (Liliaceae). It is widely distributed in the temperate zone (China, Korea, Japan) to tropical Asia (Laos and Vietnam) (Lee et al, 2019). Steroidal saponins and polysaccharides are conceived as the major chemical components of Asparagus cochinchinensis, and the content of polysaccharides was higher in roots than in stems (Xue et al, 2022).…”
Section: Introductionmentioning
confidence: 99%